A facile method to functionalize gold nano-tripods with high suspension stability in an aqueous environment. Issue 16 (11th April 2018) - Tang, T.-Y.; Wang, H.-L.; Yao, C.-T.; Yang, K.-C.; Ho, R.-M.; Tsai, D.-H.
Abstract : A facile method for preparing and characterizing Au nano-tripods with high aqueous suspension stability. Abstract : Here we aim to develop a facile emulsion-based method to prepare tripod gold nanoparticles (AuNPs) with high suspension stability in an aqueous environment. A gyroid-structured polymer template formed by the hydrolysis of a degradable block copolymer, polystyrene (PS)- b -poly(l -lactide), is used for the fabrication of AuNPs. Also, a successful emulsification of dichloromethane (DCM) in the aqueous phase is developed by using thiolated polyethylene glycol (PEG-SH) as the stabilizer. Subsequently, the nanohybrids of PS/Au can be fabricated by templated electroless plating, and then selectively dissolving in the DCM dispersive phase. Most interestingly, a dedicated process for the simultaneous release of the tripod AuNPs from the dissolution of PS associated with PEG-SH at the interface of the emulsion is achieved, giving PEG-SH-functionalized tripod AuNPs dispersed in the aqueous phase, which significantly improves the suspension stabilization of tripod AuNPs. The in situ temperature-programmed electrospray-differential mobility analysis provides a quantitative, statistical analysis of mobility diameter, dynamic shape factor, polydispersity, and colloidal stability.